Online rumors during the COVID-19 pandemic: co-evolution of themes and emotions - Shen, Chao; Song, Zhenyu; He, Pengyu; Liu, Limin; Xiong, Zhenyu (Frontiers in Public Health, 2024)
During public health emergencies, rumors spread widely on social media platforms, causing public anxiety and emotional fluctuations. Analyzing the co-evolution patterns of rumor themes and emotions on the internet is fundamental for actively and precisely managing the spread of rumors during public health emergencies. By integrating data from mainstream debunking platforms, extracting the themes and emotional characteristics of online rumors during public health emergencies, and exploring the co-evolution features of rumor themes and emotions, we can visualize the trend of theme-emotion synergy driving rumor propagation. Using the Latent Dirichlet Allocation (LDA) model, we identified five categories of rumor themes disseminated during the pandemic: epidemic prevention and control, panic-inducing, production and livelihood, virus dissemination, and social figures. According to the crisis lifecycle theory, events are categorized into outbreak, continuation, recovery, rebound, and stabilization phases, revealing the cyclical, fluctuating, and derivative nature of various theme rumors at different stages. Through sentiment analysis of rumor texts, we found that the emotions conveyed by online rumors change with the development of the epidemic. The synergistic analysis of themes and emotions indicates that rumors related to epidemic prevention and control co-evolve with positive sentiments, creating a favorable public opinion atmosphere. Conversely, panic-inducing rumors co-evolve with negative emotions, fostering a negative public opinion environment. The research findings contribute to understanding the public's focus and emotional tendencies at different stages, thereby guiding targeted public opinion guidance and crisis management.